Inheritance and the Dynamics of Party Identification - Martin Kroh; Peter Selb (Political Behavior, 2009)
Extensive research efforts notwithstanding, scholars continue to disagree on the nature and meaning of party identification. Traditionalists conceive of partisanship as a largely affective attachment to a political party that emerges in childhood through parental influences and tends to persist throughout life. The revisionist conception of partisanship is that of a running tally of party utilities that is updated based on current party performance. We attempt to reconcile both schools of thought in an individual difference perspective, showing that the party loyalties acquired through parental influences confirm better the traditional view, while the attachments of individuals who did not inherit their parents' party loyalties exhibit features more closely matching the revisionist predictions. The analysis is facilitated by uniquely suited longitudinal household data emanating from the German Socio-Economic Panel Study that allow to study party identifications of young adults and their parents on an annual basis from 1984 to 2007.
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s11109-009-9084-2
Keywords: 330; Party identification; State dependence; Trait dependence; Socialization; Germany; Dynamic panel model; Inheritance; Intergenerational transmission; Wahlverhalten; Verhaltensökonomik